Social Media Marketing Photo Techniques Training For Small And Medium Enterprises (SMEs) In Desa Kerinjing Ogan Ilir - Dessy Yunita; Aslamia Rosa; Iisnawati; Suhartini Karim (Universitas Serang Raya, 2023)
Social Media Marketing Photo Techniques Training for SMEs in Desa Kerinjing Ogan Ilir is an activity to understand photography and photo editing techniques. Within this training, SMEs are given training to develop business potential through the ability to use simple photography and editing techniques to make photos more attractive. The purpose of this training is to increase the selling value of the product. The existence of training provided to SMEs, especially in Desa Kerinjing Ogan Ilir, gives participants the ability to advance to class in the midst of intense competition.